Post-service recovery emotion and customer trust: The role of satisfaction as mediation - Resekiani Mas Bakar; Zhafran Fadhil Damara; Ahmad Yasser Mansyur (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
Service failure is inevitable, leading to the provision of a recovery method by companies to overcome customer mistrust, that creates certain emotions. This research, therefore, aims to examine the indirect effect of customer emotion on trust and service recovery mediated by satisfaction. Data were obtained from 104 participants that read the vignette on service failure and recovery. This study used the data analysis of Process Hayes to measure the role of mediation. The result showed that customer satisfaction moderated the indirect effect between emotion and trust after service failure. In addition, cognitive appraisal theory supports the interactional and procedural process used to provide positive judgment. The implication of this study is useful for companies to minimize the possibility of service failure and provide recovery in order to maintain customer trust.